Atrophy in the Thalamus But Not Cerebellum Is Specific for C9orf72 FTD and ALS Patients – An Atlas-Based Volumetric MRI Study - Schönecker, Sonja; Neuhofer, Christiane; Otto, Markus; Ludolph, Albert; Kassubek, Jan; Landwehrmeyer, Bernhard; Anderl-Straub, Sarah; Semler, Elisa; Diehl-Schmid, Janine; Prix, Catharina; Vollmar, Christian; Fortea, Juan; et al. (Frontiers in Aging Neuroscience, 2018)
Background: The neuropathology of patients with frontotemporal dementia (FTD) or amyotrophic lateral sclerosis (ALS) due to a C9orf72 mutation is characterized by two distinct types of characteristic protein depositions containing either TDP-43 or so-called dipeptide repeat proteins that extend beyond frontal and temporal regions. Thalamus and cerebellum seem to be preferentially affected by the dipeptide repeat pathology unique to C9orf72 mutation carriers. Objective: This study aimed to determine if mutation carriers showed an enhanced degree of thalamic and cerebellar atrophy compared to sporadic patients or healthy controls. Methods: Atlas-based volumetry was performed in 13 affected C9orf72 FTD, ALS and FTD/ALS patients, 45 sporadic FTD and FTD/ALS patients and 19 healthy controls. Volumes and laterality indices showing significant differences between mutation carriers and sporadic patients were subjected to binary logistic regression to determine the best predictor of mutation carrier status. Results: Compared to sporadic patients, mutation carriers showed a significant volume reduction of the thalamus, which was most striking in the occipital, temporal and prefrontal subregion of the thalamus. Disease severity measured by mini mental status examination (MMSE) and FTD modified Clinical Dementia Rating Scale Sum of Boxes (FTD-CDR-SOB) significantly correlated with volume reduction in the aforementioned thalamic subregions. No significant atrophy of cerebellar regions could be detected. A logistic regression model using the volume of the prefrontal and the laterality index of the occipital subregion of the thalamus as predictor variables resulted in an area under the curve (AUC) of 0.88 while a model using overall thalamic volume still resulted in an AUC of 0.82. Conclusion: Our data show that thalamic atrophy in C9orf72 mutation carriers goes beyond the expected atrophy in the prefrontal and temporal subregion and is in good agreement with the cortical atrophy pattern described in C9orf72 mutation carriers, indicating a retrograde degeneration of functionally connected regions. Clinical relevance of the detected thalamic atrophy is illustrated by a correlation with disease severity. Furthermore, the findings suggest MRI volumetry of the thalamus to be of high predictive value in differentiating C9orf72 mutation carriers from patients with sporadic FTD.